Eruption Pattern of Permanent Molars among School Children in Chennai (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Estimation of the age of an individual is essential investigation in medicolegal cases,especially involving children and adolescents. Among the various factors used for age estimation, eruption ofpermanent teeth is one of them. Several factors influence the eruption of teeth, including genetic, nutritionaland hormonal. This study was carried out to analyze the pattern of eruption of permanent teeth among schoolgoing children in urban Chennai.Method: This cross sectional study was carried out among 983 school children between the age groupof 4-14 years. Two schools, one belonging to the lower socioeconomic status and the other belonging tothe higher socioeconomic status were taken up for this study. Eruption of permanent teeth were examinedclinically.Results: Majority of the first molars erupted by7-7.5 years of age (95%) while majority of the centralincisors erupted between 8-9 years. Lateral incisors were completely erupted between 9.5-10 years and firstpremolar were completely erupted between 12.5-12.9 years. Both second premolar and canine erupted by13.5-13.9 years.Conclusion: The visual observation of eruption of permanent teeth is a non invasive procedure and does notrequire any special machines like that of radiography. This method of assessing the age of the individual isconsiderably easier, economical and safe. Hazards of exposing the individual to radiation can be prevented.